Relaxed optimality conditions for mu-differentiable functions - Almeida, R.
We prove some fundamental properties of mu-differentiable functions. A new notion of local minimizer and maximize is introduced and several extremum conditions are formulated using the language of nonstandard analysis. Copyright © 2009 by IJAMAS, CESER.